Crystal structure of 4-(2-hydroxy-3-methoxybenzylamino)benzoic acid dimethylformamide monosolvate monohydrate - Faizi, Md. Serajul Haque (Acta Crystallogr E Crystallogr Commun, 2019)
The title compound, C(15)H(15)NO(4)·C(3)H(7)NO·H(2)O, a secondary amine molecule, is accompanied by one equivalent of water and one equivalent of dimethylformamide (DMF) as solvents. The molecule is non-planar, with a C(aryl)—CH(2)—NH—C(aryl) torsion angle of −66.3 (3)°. In the crystal, O—H⋯O and N—H⋯O hydrogen-bonding interactions between the amine molecules and the two types of solvent molecule result in the formation of a layered structure extending parallel to (010).